Peran Lembaga Adat dalam Menerapkan Nilai-Nilai Adat di Masyarakat Adat Lamakera: Studi Kasus Orang Tua Adat Suku Pito di Lamakera - Sulaiman Mustafa Wuhdin; Afrida Deko Sega (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Culture is basically values ​​that emerge from the process of interaction between individuals. These values ​​are recognized, either directly or indirectly, over time in the interaction. This diversity is what makes Indonesia rich in customs. Through these ethnic cultures and tribes, an indigenous society is formed that occupies an area spread across Indonesia. Society is a system. Values ​​and norms grow within that society. If a society has been able to carry out its functions well, then functionally the society has been able to maintain values ​​and norms so that the life of the society can run in harmony. Customs and culture are a legacy from ancestors that must be maintained, one of which is in terms of traditional ceremonies, clothing, house shapes, social environments, livelihoods, including in religious traditions. Attitudes that used to be thick in the culture of the Indonesian nation, such as friendliness, politeness, empathy for others, the spirit of mutual cooperation, and high tolerance, seem to be fading. The approach used in this study is a qualitative approach where the data obtained comes from the field by conducting observations and in-depth interviews with informants who know and understand the problems being studied, stating that qualitative research is research that uses a natural setting, with the intention of interpreting the phenomena that occur and is carried out by involving various existing methods. The technique used in selecting informant data sources in the study, namely by using purposive sampling techniques, namely data source sampling techniques with certain considerations. The form of research used is descriptive research, namely research that describes or depicts certain situations based on data obtained in detail according to the problems set in this study.